The work of theatre artists in San Miguel of Tucumán during the decades of 1960 and 1970: independent circuit, official theatre and radio drama - Salas Tonello, Pablo (2022)
This article analyzes the work of performing artists in San Miguel de Tucumán in a modernization period during the 60’s and 70’s. This study examines the new status that artistic work achieves due to two important events: the creation of the Teatro Estable de la Provincia and the presence of specialized theatre criticisms in the most popular local journal. Then, the article explores the radio drama’s circuit, a specific field separated from independent and official theatre, characterized for productions held by an entrepreneur, the circulation of companies in the interior of the province and a large number of spectators. The article makes contributions in the understanding, from a historical perspective, of the problems and challenges faced by theatre workers in a non-metropolitan city, where the frontier between radio drama and independent and official circuits is of great relevance.